Respostas
respondido por:
3
Os outros quatro termos são:25,31,37,43.
respondido por:
5
PA = (1, 7, 13, 19....)
Razão = a2 - a1
r = a2 - a1
r = 7 - 1
r = 6
===
a8
an = a1 + ( n -1 ) . r
a8 = 1 + ( 8 -1 ) . 6
a8 = 1 + 7 . 6
a8 = 1 + 42
a8 = 43
====
an = a1 + ( n -1) . r = an
a5 = 1 + ( 5 -1) .6 = 25
a6 = 1 + ( 6 -1) .6 = 31
a7 = 1 + ( 7 -1) .6 = 37
a8 = 1 + ( 8 -1) .6 = 43
====
PA = (1, 7, 13, 19, 25, 31, 37, 43 )
Razão = a2 - a1
r = a2 - a1
r = 7 - 1
r = 6
===
a8
an = a1 + ( n -1 ) . r
a8 = 1 + ( 8 -1 ) . 6
a8 = 1 + 7 . 6
a8 = 1 + 42
a8 = 43
====
an = a1 + ( n -1) . r = an
a5 = 1 + ( 5 -1) .6 = 25
a6 = 1 + ( 6 -1) .6 = 31
a7 = 1 + ( 7 -1) .6 = 37
a8 = 1 + ( 8 -1) .6 = 43
====
PA = (1, 7, 13, 19, 25, 31, 37, 43 )
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás